Use of Rapid Drug Desensitization in Delayed Hypersensitivity Reactions to Chemotherapy and Monoclonal Antibodies - Vega, Arantza; Peña, M. Isabel; Torrado, Inés (Frontiers in Allergy, 2022)
Background: Rapid drug desensitization (RDD) allows first-line therapies in patients with immediate drug hypersensitivity reactions (DHR) to chemotherapeutic drugs (ChD) and monoclonal antibodies (mAb). Desensitization in delayed drug reactions has traditionally used slow protocols extending up to several weeks; RDD protocols have been scarcely reported. Patients and Method: We retrospectively analyzed the patients referred to the Allergy Department, who had experienced a delayed DHR (> 6 h) related to a ChD or mAb and underwent an RDD protocol. The rate of successful administration of the offending drug and the presence of adverse reactions were evaluated. Results: A total of 93 RDDs were performed in 11 patients (including 6 men and 5 women, with a median age of 61 years). The primary DHR were maculopapular exanthema (MPE) (8), generalized delayed urticaria (1), MPE with pustulosis and facial edema (1), and facial edema with desquamative eczema (1). The meantime for the onset of symptoms was 3 days (range 1–16 days). RDD was performed using a protocol involving 8–13 steps, with temozolomide (25), bendamustine (4), rituximab (9), infliximab (24), gemcitabine (23), and docetaxel (8), within 4.6–6.5 h. Sixteen breakthrough reactions were reported during the RDD (17.2 %) in 5 patients; all were mild reactions including 11 delayed and 5 immediate reactions. All patients completed their treatment. Conclusions: RDD is a potentially safe and effective procedure in patients suffering from delayed reactions to ChD and mAb. It allows them to receive full treatment in a short period, thereby reducing time and hospital visits.